Fancy Bear goes phishing : the dark history of the information age, in five extraordinary hacks - Shapiro, Scott (New York : Allen Lane ,Penguin Books, 2023)
"A law professor and computer expert's take on how hacks happen and how the Internet can be made more secure"--
Includes bibliographical references and index.
Keywords: Hacking -- Case studies; Phishing -- Case studies